DEVELOPMENT OF TECHNOLOGY-BASED ASSESSMENT INSTRUMENTS IN SCIENCE LEARNING: A NARRATIVE REVIEW (2015-2025) - Yul Ifda Tanjung; Tiur Malasari Siregar; Suci Frisnoiry; Elfitra Elfitra; Taufiq Ramadhan; Abil Mansyur; Rizky Agassy Sihombing (JURNAL EDUSCIENCE, 2026)
Purpose - This study critically synthesizes research on the development of technology-based assessment instruments in secondary science education (junior and senior high school) through a structured Narrative Literature Review (NLR). This review therefore identifies instrument types, implementation contexts, research dimensions examined, and learning impacts, while highlighting gaps in equity, teacher readiness, and longitudinal outcomes.Methodology - Articles were systematically retrieved from Google Scholar and Mendeley within the 2015–2025 publication range using predefined keywords related to technology-based assessment and science learning. Inclusion criteria required peer-reviewed empirical studies focusing on secondary-level science and reporting instrument development or evaluation. Fourteen eligible articles were analyzed using structured content analysis, with emphasis on instrument characteristics, evidence of validity and reliability, implementation contexts, methodological approaches, and reported limitations.Findings - The synthesis indicates that research predominantly centers on Computer-Based Testing (CBT), Computerized Adaptive Testing (CAT), gamified assessments, two-tier diagnostic tests, and LMS-based e-portfolios. Overall, these instruments demonstrate satisfactory validity and reliability and effectively measure higher-order thinking skills and conceptual understanding. They also enhance student motivation and accelerate feedback processes. However, most evidence is based on short-term, small-scale implementations, with limited attention to equity issues, teacher readiness, and sustained learning effects.Contribution - This review integrates psychometric, pedagogical, and technological perspectives into a coherent analytical framework for technology-based assessment in science education. It clarifies existing research gaps and underscores the need for broader contextual validation, stronger methodological rigor, and the integration of learning analytics to ensure sustainable and evidence-based digital assessment practices.